RESEARCH OF THE IMPACT OF PACKAGING MATERIALS AND RECIPE INGREDIENTS FOR THE CONSERVATION OF THE CONSUMPTION PROPERTIES OF GINGERBREADS, CEREAL PUFFS AND DRY BREAKFASTS DURING THEIR STORAGE - Bodak Mykhailo; Gyrka Olga (Sciemcee Publishing, 2019)
The influence of various factors on the preservation of the consumer properties of new products has been examined. The dynamics of changes in organoleptic quality indicators, moisture content, and the peroxide value of fat in the developed products during storage have been studied, and their shelf life has been determined. The relationship between chemical composition, type of packaging material, storage conditions, and shelf life of gingerbread, cereal sticks, and breakfast cereals has been demonstrated. The effectiveness of using polypropylene packaging to inhibit oxidative processes and reduce moisture loss in gingerbread has been proven. The feasibility of using multilayer film materials—polyethylene terephthalate (PET), non-oriented polypropylene, and metallized biaxially oriented polypropylene GM-200 (BOPP)—during the storage of cereal sticks and breakfast cereals has been established.
Bodak M. Resefrch of the impact of packaging materials and recipe sngredients for the conservation of the consumption properties of gingerbreads, cereal puffs and dry breakfasts during their storage : колективна монографія / M. Bodak, O. Gyrka. Modern world tendencies in the development of science. – London, 2019. – Volume 2. – P. 190-206. (ISBN 978-1-9993071-4-1).
Keywords: gingerbread; packaging materials; polypropylene; moisture loss; peroxide value of fat; breakfast cereals